"One language and one tongue": Animal speech in Jubilees 3:27–31. (June 2019) - Wells, A Rahel
Jubilees 3:27–31 explains the command to cover one's nakedness, and the connections with animal speech help to elucidate the reasons for this law. Jubilees implies a sort of equality/solidarity between humans and animals due to their sin/impurity. Even though God does not directly address the serpent with speech, Jubilees portrays animals as more rational than in Genesis, as they originally talked and conversed with each other and apparently also with humans. This shared rationality and identity between all animals results in all losing their speech. Animals are portrayed in Jubilees with more rationality, culpability, and even solidarity with humans than in Genesis. The one exception is that animals are not allowed to cover their nakedness, and yet they still end up in a more positive light than the nations, who are willfully uncovered and in shame.